Legal Protection for Medical Personnel in Providing Clinical Services Through Telemedicine Based on Law of the Republic of Indonesia Number 17 of 2023 Concerning Health - Masbuhin Masbuhin; Achmad Sulchan (UNISSULA Semarang, 2025)
Abstract. Advances in information technology have driven the adoption of telemedicine as a new method of clinical service delivery, offering greater accessibility and efficiency. However, the implementation of telemedicine, which involves long-distance communication and technological complexity, raises crucial issues regarding the responsibilities and legal protections of medical personnel. This research is relevant in light of the enactment of Law Number 17 of 2023 concerning Health, which serves as the latest legal basis for regulating the health ecosystem in Indonesia, including telemedicine. This study aims to analyze and identify the form and scope of legal protection provided to medical personnel in providing clinical services via telemedicine, based on the provisions stipulated in Law of the Republic of Indonesia Number 17 of 2023 concerning Health. Furthermore, this study also examines the potential legal risks faced by medical personnel and the implications of the latest Health Law in ensuring legal certainty for telemedicine practices. This research employs a normative legal research method, with a statute approach and a conceptual approach. Data sources include primary legal materials (primarily Law No. 17 of 2023), secondary legal materials (literature, journals, and related legal documents), and tertiary legal materials. The analysis was conducted qualitatively and descriptively to draw logical and solution-oriented conclusions. The research findings show that Law No. 17 of 2023 explicitly recognizes and regulates the implementation of telemedicine as part of the health transformation. Legal protection for medical personnel is accommodated through more comprehensive regulations regarding professional service standards, practice permits, electronic medical records, and guarantees related to the handling of complaints and disputes. However, this research identified gaps or ambiguities in technical regulations regarding the authority and limitations of cross-regional/national telemedicine practices, as well as protection against diagnostic/therapeutic errors influenced by technological limitations, which have the potential to pose legal risks. Law No. 17 of 2023 concerning Health provides a stronger foundation for legal protection for medical personnel in telemedicine practices, but needs to be followed up with detailed and clear implementing regulations. Effective legal protection requires a synergy between strong regulations, the implementation of strict professional standards, and the use of technology that ensures data security and patient confidentiality.